Common Microorganisms Present in Diabetic Foot Infection and It’s Spectrum of Antibiotic Sensitivity - Rahman, Md Ziaur; Uddin , Mir Jalal; Mollah , Abdul Hamid; khan, Himika Hasan; Kabir , AKM Ziaul (Medicine Today, 2022)
Introduction: Diabetic patients have foot problems secondary to neuropathy, micro-vascular changes and impaired resistance to infection. They are at increased risk of infection and ulceration. Diabetic ulcers are frequently involved in both aerobe and anaerobe microorganisms. It is important to culture the specimen on several different media. The Gram stain can provide valuable information regarding the range of organisms under consideration. The aim of this study is to identify the sensitive antibiotics to the specific aerobic bacteria, to prevent the random misuse of broad spectrum antibiotics and make awareness about diabetic foot care. Materials and Methods: This study was a retrospective analysis and was carried out in general surgery and diabetic wards at North Bengal Medical College Hospital (NBMCH), Sirajganj, Bangladesh from August, 2019 to July, 2020. To identify common aerobic microorganism and spectrum of antibiotic sensitivity from 54 cases of diabetic foot ulcers, wound swabs taken and cultured using standard aerobic microbiological techniques. Antibiotic sensitivity testing to different antimicrobial agents were carried out using the disc diffusion method. Result: Among 54 aerobic bacterial isolates, Gram negative bacteria 41(75.9%) and Gram positive bacteria 13(24.1%). Escherichia Coli 28(51.9%), Proteus spp 09(16.7%), Pseudomonas 03(5.6%), Klebsiella spp 01(1.9%) were isolated Gram negative bacteria. Staphylococcus aureus 13(24.1%) was only Gram positive bacteria. Gram negative bacterial isolates were sensitive to Imipenem, while Vancomycin showed good activity against Gram positive bacteria. Conclusion: The antibiogram results of this study suggest that bacteria remain sensitive to a limited number of used agents, while found resistant to a number of widely used agents. Imipenem was most effective against Gram negative bacilli and also effective against Gram positive cocci. Medicine Today 2022 Vol.34(1): 65-69